The Need to Teach Natural Medicine in Educational Institutions to Prevent Health Risks in Children and Adolescents - Cano-Ortiz, Ana; Cano, Eusebio (Journal of Ecohumanism, 2025)
The aim of this theoretical-practical study is to alert families to the excessive and improper use of medicinal plants. Our sociological analysis reveals a high consumption of plants with medicinal interest; however, society remains largely unaware of the potential consequences of their use, indicating a clear lack of knowledge regarding medicinal species. While this form of medicine is widely used, it is neither medically supervised nor adequately regulated by pharmaceutical authorities. The species being consumed, their potential adulterations, and possible falsifications are often unknown. The widespread use of these plants is largely driven by oral transmission within communities and by commercial advertising. From an educational perspective, the teaching of medicinal plant use is not included in student curricula, highlighting the need for its integration into formal education. To enhance knowledge of medicinal plants, we provide an overview of some widely used species with therapeutic applications in digestive disorders, liver conditions, cholesterol regulation, blood glucose levels, blood pressure control, weight management, and respiratory ailments. The inclusion of frequently used species aims to contribute a glossary of scientific terms, promoting scientific literacy and raising social awareness regarding the responsible use of natural medicine.